Examining urban school principals' perceptions and insights on the bidirectionality of engagement: a case study of school district leaders. (8th August 2022) - Johnson, Detra D.; Hooper, Lisa M.; Spikes, Daniel D.; Carpenter, Bradley W.; Bowers, Amanda; Jean-Marie, Gaëtane
ABSTRACT: Limited culturally responsive knowledge, skills, and engagement among school leaders contributes to significant racial disparities seen in diverse student outcomes (school pushout, rates in school discipline, and opportunity gap) and remains a pernicious problem for public schools in the United States. Also, school leaders and teachers often lack authentic engagement contributes to a sense of belongingness and connectedness among students, families, and school staff and systems. Thus, the primary purpose of the study was to explore principals' beliefs and insights about both school leaders' and students' engagement behaviours and their contribution to cultural competence, school climate, and educational achievement. Qualitative data were collected using structured interviews with 40 school leaders from a large urban school district located in the mid-West. Thematic coding was used to analyse the data and emergent themes were identified based on principals' responses. Results derived from their narratives and data analysis generated five major themes. The findings cohered with the existing literature related to communication methods, professional development trainings, and ways of being that impede and facilitate cultural competence, school climate, and leader and student engagement. Preliminary recommendations for future research and practice are offered.